Optimizing the Role of Teachers in Strengthening Character Education to Prevent Bullying Behavior in the School Environment - Nurjanah, Sri; Cahya, Albin Dwi; Raharja, Reza Mauldy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
We conducted research to find out the role of teachers in optimizing the character of education in the school environment so that bullying behavior does not occur at school. In the school where we researched, we did not find any bullying carried out by students, but we focused more on the role of teachers in strengthening the character of education so that there is always no bullying in the school environment. We conducted research at SMAN 4 Cibinong and SMPN 4 Serang City schools, which schools are in Serang City and Bogor Regency. For the method used we used qualitative research methods, where the data collection technique we used was using interviews. and observation, then apart from that also the data source, namely online via TV and social media as well as the results of the observations we made. At the school where we researched, we have carried out character education activities, which include praying Dhuha together, applying the 5s, namely smiling, greeting, saying hello, being polite and courteous. Apart from that, listening to teachers in giving advice before lessons start, education in schools can prevent bullying. The school where we conducted our research did not want its students to become perpetrators or even victims of bullying.